2023
DOI: 10.1111/radm.12634
|View full text |Cite
|
Sign up to set email alerts
|

The role of entrepreneurial ecosystems in technological and social challenges

Abstract: Although there is a common consensus about what an entrepreneurial ecosystem (EE) is, the question of how EE dynamics interact with technology and social change remains unclear. In this introductory article to our Special Issue on the role of EE in technological and social challenges, we systematically review the corpus of literature in this field of research. Leveraging bibliometric techniques, we present a review of the most influential papers and their key research topics, synthesized across four thematic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…Innovation thrives in an environment that encourages knowledge exchange, collaboration, and interdisciplinary research (Hou et al 2019). Collaboration between academia, industry, and government is vital for fostering innovation (Ferreira et al 2023). Effective knowledge transfer mechanisms, such as research partnerships, technology transfer offices, and incubators, enable the translation of scientific discoveries into practical applications (Castañer and Oliveira 2020).…”
Section: Innovation and Serial Innovationmentioning
confidence: 99%
“…Innovation thrives in an environment that encourages knowledge exchange, collaboration, and interdisciplinary research (Hou et al 2019). Collaboration between academia, industry, and government is vital for fostering innovation (Ferreira et al 2023). Effective knowledge transfer mechanisms, such as research partnerships, technology transfer offices, and incubators, enable the translation of scientific discoveries into practical applications (Castañer and Oliveira 2020).…”
Section: Innovation and Serial Innovationmentioning
confidence: 99%
“…Current understandings of the EE concept, then, amount to a one-size-fits-all general theory of EEs, driven by broad guidelines, that does not properly consider context and variation along the lines of actor roles or sectoral activity. More research is needed to identify ways in which EEs may differ (see, for example, Ferreira et al, 2023) and exploring their connections with clusters. By questioning these distinctions between EEs and clusters we have shown that the EE concept has considerable conceptual ambiguity within its internal definitions but also in its demarcations with other concepts, reifying its position as a chaotic concept.…”
Section: The Conceptual Ambiguity Between Entrepreneurial Ecosystems ...mentioning
confidence: 99%
“…Stanford, Harvard) help populate the market with strong human capital, and as a result these regions also attract the interest of both individual and institutional investors with the capital necessary for venturing. An abundance of entrepreneurs ensures healthy competition, while early technology adopters provide a reliable customer base eager for innovation (cf., Bakry et al, 2022;Ferreira et al, 2023). The synergistic effect of these market interactions in places like Silicon Valley and Boston underscores their efficacy as thriving entrepreneurial ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…An abundance of entrepreneurs ensures healthy competition, while early technology adopters provide a reliable customer base eager for innovation (cf., Bakry et al. , 2022; Ferreira et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%